2005
DOI: 10.4315/0362-028x-68.11.2480
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Depletion of Marbofloxacin Residues in Rabbit after Therapeutic Treatment

Abstract: Although rabbit meat production represents a very small percentage of the world meat market, this percentage has been growing continuously during the last 30 years. Rabbit is considered a minor food species, and therefore no drugs are specifically registered for this animal. This situation encourages rabbit farmers to make off-label use of antibacterial drugs authorized for food-producing animal species other than rabbits. In the present study, the distribution and elimination of the fluoroquinolone antibacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 10 publications
2
4
2
Order By: Relevance
“…This finding is in agreement with Ligabue et al [17] who reported that marbofloxacin in rabbits' muscle was lower than those measured in the liver and kidney after S.C injection at a dose of 2mg/kg BW/day for 5 days. We found that marbofloxacin residues concentrations in muscles at the 1 st day and in kidneys and livers at the 3 rd day were lower than the MRL (150 µg/kg) recommended by EMEA [20].…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…This finding is in agreement with Ligabue et al [17] who reported that marbofloxacin in rabbits' muscle was lower than those measured in the liver and kidney after S.C injection at a dose of 2mg/kg BW/day for 5 days. We found that marbofloxacin residues concentrations in muscles at the 1 st day and in kidneys and livers at the 3 rd day were lower than the MRL (150 µg/kg) recommended by EMEA [20].…”
Section: Discussionsupporting
confidence: 83%
“…The results obtained in the present study confirmed that the absorption and distribution of marbofloxacin administered to rabbits via intramuscular injection reach high levels in a short time in kidney, liver, lung and muscle which were in agreement with the previous reports [10, 16,17,19]. Marbofloxacin remained within the detectable limit till the 5 th day in most tested tissues, while in kidney it remained till the 7 th day following last administration of the drug.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations